Social Networking in Higher Education Saudi Arabia Perspective - Almufaraj, W.; Issa, Tomayess (CRC Press, 2018)
Traditional algorithm software cannot deal with such complex and vast amounts of data, necessitating the development of novel analytic approaches and tools. This reference work deals with social network aspects ofbig data analytics.